(untitled) (Bangladesh Journal of Animal Science, 2013)
The experiment was conducted to evaluate the performance of buck on the basis of semen quality and fertility. Data on 162 ejaculates from five adult Black Bengal bucks (B1, B2, B3, B4 and B5) were recorded. Individual buck effect was found to be significant on semen volume (p<0.05), three stages of sperm motility (p<0.01) and percentage of live sperm (p<0.01) but insignificant (p>0.05) on sperm concentration and percentage of normal sperm. The results of semen volume per ejaculate, sperm concentration, initial sperm motility, on dilution sperm motility, post-thawing sperm motility, percentage of live sperm and percentage of normal sperm were ranged from 0.58±0.17 to 1.04±1.1 ml, 2827±0.76 to 3132